2022
DOI: 10.3390/foods11172658
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Volatile Compounds during Ripening and Final Sensory Changes of Traditional Raw Ewe’s Milk Cheese “Torta del Casar” Maturated with Selected Protective Lactic Acid Bacteria

Abstract: In traditional soft ripened cheeses made with raw milk, the use of protective cultures is infrequent. In the present work, the effect of selected (for their activity against Listeria monocytogenes) protective cultures of Lactocaseibacillus casei 116 and Lactococcus garvieae 151 was evaluated, on the evolution of volatile compounds throughout the ripening and on the final sensory characteristics of traditional soft ripened “Torta del Casar” cheese. For this, both strains were separately inoculated in raw cheese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Furthermore, Martín et al [ 86 ] demonstrated that the inoculation of this strain did not modify the sensory characteristics of dry-cured fermented sausages. L. casei 116 caused a decrease in L. monocytogenes of 2.2 log CFU g −1 when it was inoculated in short-ripening traditional cheeses without modifying their sensory properties [ 66 , 87 ]. Margalho et al [ 67 ] indicated that greater than 3 log reduction in L. monocytogenes in Brazilian artisanal cheeses can be achieved using L. plantarum (1QB77) after 21 days of ripening.…”
Section: Pathogenic Bacteria In Ripened Foods and Biocontrol Strategiesmentioning
confidence: 99%
“…Furthermore, Martín et al [ 86 ] demonstrated that the inoculation of this strain did not modify the sensory characteristics of dry-cured fermented sausages. L. casei 116 caused a decrease in L. monocytogenes of 2.2 log CFU g −1 when it was inoculated in short-ripening traditional cheeses without modifying their sensory properties [ 66 , 87 ]. Margalho et al [ 67 ] indicated that greater than 3 log reduction in L. monocytogenes in Brazilian artisanal cheeses can be achieved using L. plantarum (1QB77) after 21 days of ripening.…”
Section: Pathogenic Bacteria In Ripened Foods and Biocontrol Strategiesmentioning
confidence: 99%
“…A group of volatile sulfur compounds (VSCs) has been recognized as responsible for cheese flavor [ 74 ]. Most of these compounds are derivatives of the degradation of the sulfur-carbon bond of methionine to form methanethiol (MTL).…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…The reduction of methionine catabolism by cysteine in Arthrobacter spp. could be caused by a reduction in MGL activity due either to a direct effect of high concentrations of cysteine or to other enzymes [ 74 ]…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%
“…It has been proven that dairy-related strains are lactose fermenters, despite the relatively slow acidification rate [69] (Table 3). Their presence does not affect the main physicochemical properties such as humidity, water activity, pH, texture, or color while contributing positively to the aroma with the production of methyl-branched acids and reducing the oxidation compounds originating from the β-oxidation of fatty acids present within the milk [70]. coagulation of the milk proteins [53,80] organoleptic properties [23,81] M. sciuri organoleptic properties [94][95][96] no definitive data Inhibitory activity against pathogens and spoiling agents has also been reported for some dairy L. garvieae strains.…”
Section: Lactococcus Garvieaementioning
confidence: 99%